Quantifying the Burden of Shoulder and Hip Pain In Water Polo Players Across Different Playing Levels - Michael Girdwood (North American Sports Medicine Institute, 2021)
# Background Water polo is characterised by unique skills and movements with high demands of both the upper and lower limb. There is growing recognition of the problems of shoulder and hip/groin symptoms in this population.